Pengaruh Jarak Tanam dan Aplikasi Dosis Pupuk NPK Terhadap Hasil Tanaman Kacang Panjang (Vigna sinensis L.) - Giawa, Suci Citrawani; Harahap, Lutfi Henderlan (UNIVERSITAS LABUHANBATU, 2024)
This study aimed to analyze the interaction between planting distance and NPK fertilizer dose onthe growth and yield of long bean plants. The experimental design used a factorial RandomizedComplete Block Design (RCBD) with two factors, namely planting distance (30 cm x 20 cm, 30cm x 30 cm, and 30 cm x 40 cm) and NPK fertilizer dose (0 gr/polybag, 40 gr/polybag, and 60gr/polybag).Theobservedvariablesincludedplantheight,stemdiameter,podlength,podweight, and number of pods. The data were analyzed using ANOVA and Duncan's MultipleRange Test at the 5% level. The results showed that there was a significant interaction betweenplantingdistanceandNPKfertilizerdoseontheyieldoflongbeanplants.Thecombinationof30 cm x 30 cm planting distance and 60 gr/polybag NPK dose (P2J2) produced the best results,especiallyintermsofpod weight andnumberofpods perplant. Keywords:longbean,plantingdistance,NPKfertilizer